Oxygen Adsorption Kinetics Study used Pressure Swing Adsorber (PSA) for Nitrogen Production. (February 2019) - Purnamasari, I; Yerizam, M; Hasan, A; Junaidi, R
Abstract: One of the methods for air separation to get nitrogen gas is using the Pressure Swing Adsorption (PSA). Adsorption is a separation process to adsorb oxygen and release nitrogen as a product. This research aims to study the equilibrium and kinetics that occur in the oxygen adsorption using carbon sieve molecular (CMS) as an adsorbent. Air flowed through the compressor to PSA, air pressure (4 - 7 bar) and absorption time (3 - 9 minutes) were observed. The results showed that the higher pressure, the lower nitrogen purity. The highest nitrogen purity is 96.2% that produced at 4 bar pressure in 7 minutes. The adsorption equilibrium fits well to Temkin isotherm with R 2 = 0.9938, Temkin isotherm constant (b) = 63.203 × 10 3, Temkin isotherm equilibrium binding constant (A) = 1.00 L/g, and Constant related to heat of sorption (B) = 0.03 92 J/mol. First order pseudo model kinetics is suitable for oxygen adsorption processes. The value of adsorption rate constants are vary around (4, 5, 6 and 7 bar pressure) : 0.8089 min −1, 0.203 min −1, 0.3476 min −1, and 0.6668 min −1 with R 2 = 1.